2020
DOI: 10.1177/1010539520909942
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Residues in Chickens and Farmers’ Knowledge of Their Use in Tay Ninh Province, Vietnam, in 2017

Abstract: Antibiotic residues in chicken meat samples is a serious public health concern due to their harmful effects on consumers’ health. We conducted this research in 2017 to determine antibiotic residues in chicken meat samples and to describe the knowledge, attitude, and practice (KAP) of farmers on the antibiotic uses in poultry farms at Tay Ninh province. Farmers who raised chickens at their farmhouses were surveyed using a KAP survey questionnaire, and 106 chicken meat samples were analyzed for 29 kinds of antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…For a clearer evaluation, all studies with salmon, other fish from aquaculture, and shrimp were combined as seafood in the evaluation, as can be seen in Figure 2 . Cattle [ 17 , 18 , 19 , 20 , 21 , 22 ], Eggs [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], Milk [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ], Pork [ 58 , 59 , 60 ], Poultry [ 58 , 59 , 60 , 61 , 62 , 63 , 64 ,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For a clearer evaluation, all studies with salmon, other fish from aquaculture, and shrimp were combined as seafood in the evaluation, as can be seen in Figure 2 . Cattle [ 17 , 18 , 19 , 20 , 21 , 22 ], Eggs [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], Milk [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ], Pork [ 58 , 59 , 60 ], Poultry [ 58 , 59 , 60 , 61 , 62 , 63 , 64 ,…”
Section: Resultsmentioning
confidence: 99%
“…The data from the combined papers were divided For a clearer evaluation, all studies with salmon, other fish from aquaculture, and shrimp were combined as seafood in the evaluation, as can be seen in Figure 2. Cattle [17][18][19][20][21][22], Eggs [23][24][25][26][27][28][29][30], Milk , Pork [58][59][60], Poultry [58][59][60][61][62][63][64][65][66][67], Sheep [68] and seafood [58,[69][70][71][72][73][74][75][76][77][78][79][80][81][82][83]. Combined analysis of more than one animal product was very common for pork, poultry, and seafood [63,[84][85]…”
Section: Resultsmentioning
confidence: 99%
“…In developing countries, there is limited access to correct, credible information and satisfactory training about prudent AMU and AMR. 21 , 24 , 50 , 56 , 65 , 101 , 110 , 115 However, a lack of access to credible, reliable information is not isolated to developing countries, as farmers in the UK also reported a scarcity of communication and information available on antimicrobials. 37 , 81 In Ethiopia, many of the respondents were illiterate and therefore could not read proper dispensing instructions in relation to dose and storage.…”
Section: Resultsmentioning
confidence: 99%
“…Several European studies indicated that ease of administration and the farmer’s ability to administer antimicrobials appropriately governed vets’ treatment choices. 65 , 115 , 117 , 122 Similarly, in India and Italy, the administration route and withdrawal periods were considered, particularly for intensive sectors i.e. porcine.…”
Section: Resultsmentioning
confidence: 99%
“…Worse still, the massive use of antibiotics has a negative impact on human food security . A report on the analysis of 29 antibiotic residues in 106 chicken samples in Tay Ninh Province of Vietnam in 2017 showed an astounding 27.4% antibiotic residue rate in chicken . It is the emergence of drug-resistant bacteria and the problem of antibiotic residues that has led to the introduction of antibiotic ban policies worldwide. , An ongoing paradox in the livestock industry is that the use of antibiotics could maintain livestock production levels to some extent, and vice versa decrease. , However, simultaneously, antibiotics may bring about food safety problems.…”
Section: Discussionmentioning
confidence: 99%